Karakteristik Intake Kalori dan Gula Darah pada Penderita Diabetes II yang Berpuasa Ramadhan dan Tidak Berpuasa Ramadhan - Ali Santosa (Jurnal Ilmu Kesehatan Masyarakat, 2014)
Fasting is unfavorable situation for people with diabetes mellitus (DM) type 2 because it can lead to hyperglycemia and hypoglycemia when breaking before breaking the fast. Therefore, setting the proper feeding schedule, the amount of calories consumed, as well as administration and dosage schedules should be adjusted when the patient fasting. Types of observational studies with treatment of patients with type 2 diabetes who Ramadan fasting through consecutive sampling. One group of data taken during fasting compared to 2 months later the same group of data taken when non fasting. The data retrieved is the number of calories consumed daily and blood glucose levels sunset, 2 hours after sunset meals, predawn, and 2 hours postmeal. Based on the test paired samples T-test in patients with type 2 diabetes obtained significant differences in caloric intake while fasting against nonfasting  (p-value<0.05). The pattern also shows differences in caloric intake during after the sunset meals (69 %) compared to when the predawn (31 %). Blood glucose levels found significant differences between the fasting and nonfasting (p-value<0.05). Mean blood glucose levels when not fasting total of 190.05 mg/dl higher than the mean fasting total of 168.22 mg/dl. When fasting blood glucose levels rise in average at sunset meals and predawn of 75.11 mg/dl and 59.84 mg/dl respectively. When nonfasting blood glucose rise at breakfast higher at 63.08 mg/dl than at dinner by 24.46 mg/dl. Incidence of hypoglycemia during fasting four times as many (10.8%) than when nonfasting (2.7%). Patients with type 2 diabetes mellitus is obtained: the number of calories and blood glucose profile that fasting is lower than that is nonfasting; there is a positive relationship between the rise in blood sugar to rise in the level of calories. Ramadan fasting in patients with type 2 diabetes mellitus is positive dietary therapy but little risk of mild hypoglycemia when sunset and hyperlycemia when sunset meals. Keywords : Diabetes Mellitus II, fasting Ramadan , calories, blood glucose profiles, hypoglycemia.